Odpowiedzi

2009-08-10T15:07:47+02:00
(x-1)²=x²-2x+1
(2a - 3)²=4a²-12a+9
(a+3)²=a²+6a+9
(x-2)³=x³-6x²+12x-8
(a-6)²=a²-12a+36
(x+4)³=x³ + 12x² + 16x + 60
(2x-4)³=8x³ - 8x² + 180x - 60
(3a + 2b)³=9a³ + 54a²b + 36ab² - 8b³
(1/2x - 3/2)³=1/8x³ - 2 ¹/₄x² + 2 ¹/₄x - 3 ⁷/₈
(4a - 5)(4a +5)=16a²-25
(x²- 1/3y)(x² + 1/3y) =4x² - 1/9y²
2009-08-10T15:14:36+02:00
(x-1)² = x² - 2x + 1
(2a-3)² = 4a² - 12a + 9
(a+3)² = a² + 6a + 9
(x-2)³ = x³ - 6x² + 12x - 8
(a-6)² = a² - 12a + 36
(x+4)³ = x³ + 12x² + 16x + 60
(2x-4)³ = 8x³ - 8x² + 180x - 60
(3a+2b)³ = 9a³ + 54a²b + 36ab² - 8b³
(1/2x - 3/2)³ = 1/8x³ - 2 1/4x² + 2 1/4x - 3 7/8
(4a-5)(4a+5) = 16a² - 25
(x2 - 1/3y)(x2 + 1/3y) = 4x² - 1/9y²